As escolas paroquiais capuchinhas no interior do Maranhão (1960-1970) - CARDOSO, Janeth Carvalho da Silva (2018)
This study is part of the history of Brazilian educational institutions and seeks to analyze the pedagogical action of the Lombard Capuchins in parochial schools in the interior of Maranhão in the period from 1960 to 1970. The research of the documentary type and field, supported in the bibliographical revision with a qualitative approach is linked to the research group history and Memory of Maranhão Education (GHIMEM) and the nucleus of studies and documentation in history of education and practices Readers (NEDHEL), of the PostGraduate program in Education of the Federal University of Maranhão. From the theoreticalmethodological approach of the new cultural history, it was sought to identify the pedagogical activities of the capuchins in the interior of Maranhão, as well as to verify the organization of the parish schools created by the Capuchins, Theoretical reference among other Bourdieu authors (2013); Chartier, (1990); Certeau (2014); Hunt, (2001); Castro Castellanos Fancy, (2012) and Nunes, (2005). The sources such as Tombo books, parish schools statutes and annual reports of the religious are among the documents that were selected for the analysis, according to the proposed objectives. The critical analysis of the sources was made from the representations of the social world through its forms and motives, with the aim of achieving a closer approximation of the real from the understanding of those who produced the documents, which the interests of the groups that the They forged and the position of those who gave them, thus enabling the construction of a knowledge that allowed us to establish relations with society and with the thought of the time in focus, contributing to the understanding of an important part of the history of Maranhão education. For this reason, the former and expupils of parish schools of the period chosen for study were also carried out, thus allowing to highlight the existence of a network of parochial schools capuchin that offered the The same time primary education and catechesis as instruments of strengthening Catholicism and fighting Protestantism in the interior of Maranhão in the second half of the twentieth century.